2008
DOI: 10.1007/s00418-008-0476-x
|View full text |Cite
|
Sign up to set email alerts
|

A long-term study on female mice fed on a genetically modified soybean: effects on liver ageing

Abstract: Liver represents a suitable model for monitoring the effects of a diet, due to its key role in controlling the whole metabolism. Although no direct evidence has been reported so far that genetically modified (GM) food may affect health, previous studies on hepatocytes from young female mice fed on GM soybean demonstrated nuclear modifications involving transcription and splicing pathways. In this study, the effects of this diet were studied on liver of old female mice in order to elucidate possible interferenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
49
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 69 publications
6
49
0
1
Order By: Relevance
“…In particular, GM-fed mice show irregularly shaped nuclei, which generally represents an index of high metabolic rate, and a higher number of nuclear pores, suggesting intense molecular trafficking. More recently, the same authors (Malatesta et al, 2008) showed that several proteins belonging to hepatocyte metabolism, stress response, calcium signalling and mitochondria were expressed in 24-month-old female mice fed on GM soybean, indicating a more marked expression of senescence markers in comparison to controls. Moreover, hepatocytes of GM-fed mice showed mitochondrial and nuclear modifications indicative of reduced metabolic rates.…”
Section: Introductionmentioning
confidence: 96%
“…In particular, GM-fed mice show irregularly shaped nuclei, which generally represents an index of high metabolic rate, and a higher number of nuclear pores, suggesting intense molecular trafficking. More recently, the same authors (Malatesta et al, 2008) showed that several proteins belonging to hepatocyte metabolism, stress response, calcium signalling and mitochondria were expressed in 24-month-old female mice fed on GM soybean, indicating a more marked expression of senescence markers in comparison to controls. Moreover, hepatocytes of GM-fed mice showed mitochondrial and nuclear modifications indicative of reduced metabolic rates.…”
Section: Introductionmentioning
confidence: 96%
“…Prescott et al (2005), in the diet of rats as GM foods, they used GM Bt peas variety and found that GM insecticidal proteins act of falling immunity and appearance of allergic reactions. Malatesta et al (2002), Malatesta et al (2003), Malatesta M et al (2008), Vecchio et al (2004), Tudisco et al (2006), Brasil et al (2009), in the diet of mice and rabbits as GM foods they used GM soybeans and established disorders on the liver, pancreatic and testicular function, disturbances of the function of enzymes in the kidneys and heart changes in the uterus. Duggan et al (2003), in the diet of rats as GM foods they used GM Bt corn and established higher levels of certain fats (triglycerides) in the blood, problems with liver function, the kidneys and was disturbed excretion of certain minerals, changes in biochemical image of blood, disorders in the immune system.…”
Section: Resultsmentioning
confidence: 99%
“…GM-fed mice showed mitochondrial and nuclear modifications indicative of reduced metabolic rate Malatesta et al (2008a) Mice -No morphological differences in embryos of GM and non-Gm soybeanexposed groups. Microscopic and ultramicroscopic cellular changes attributed to GM soybean intake Cisterna et al (2008) Wistar rats 30 days…”
Section: Effects On Animal Health Of Gm Soybeanmentioning
confidence: 95%
“…It was concluded that GM-HRA protein is safe when used in agricultural biotechnology. In contrast to the above results, in a long-term study on female mice fed with a GM modified soybean (insertion of the bacterial CP4 EPSPS gene to confer a high level of tolerance to glyphosate), focused on assessing the effects of this diet on liver of old animals (until 24 months of age) and to elucidate possible interference with aging, Malatesta et al (2008a) found that GM soybean intake could influence the liver morpho-functional features during the physiological process of aging. Several proteins belonging to hepatocyte metabolism, stress response, calcium signaling and mitochondria were differentially expressed in GM-fed mice, indicating a more marked expression of senescence markers in comparison to controls.…”
Section: Effects On Animal Health Of Gm Soybeanmentioning
confidence: 99%